2015
DOI: 10.1038/srep09058
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging with Superparamagnetic Iron Oxide Fails to Track the Long-term Fate of Mesenchymal Stem Cells Transplanted into Heart

Abstract: MRI for in vivo stem cell tracking remains controversial. Here we tested the hypothesis that MRI can track the long-term fate of the superparamagnetic iron oxide (SPIO) nanoparticles labelled mesenchymal stem cells (MSCs) following intramyocardially injection in AMI rats. MSCs (1 × 106) from male rats doubly labeled with SPIO and DAPI were injected 2 weeks after myocardial infarction. The control group received cell-free media injection. In vivo serial MRI was performed at 24 hours before cell delivery (baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 29 publications
5
42
1
Order By: Relevance
“…This finding has not been reported in previous studies on myocardial infarction. 13,14,16 As histology revealed a remarkable cell apoptosis at 1 week after transplantation, the apoptosis of grafted cells might mainly contribute to the drop of such low signal volume. Our results also showed that a small fraction of MSCs can survive for a long period of 8 weeks after transplantation.…”
Section: Duan Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…This finding has not been reported in previous studies on myocardial infarction. 13,14,16 As histology revealed a remarkable cell apoptosis at 1 week after transplantation, the apoptosis of grafted cells might mainly contribute to the drop of such low signal volume. Our results also showed that a small fraction of MSCs can survive for a long period of 8 weeks after transplantation.…”
Section: Duan Et Almentioning
confidence: 99%
“…9,13,16,17 It has been reported that SPIONbased MRI cannot provide reliable information on long-term viability and might overestimate the survival of SPIONlabeled stem cells in myocardial infarction. 13,14 In our study, the dynamic change of low signal volume on MRI was consistent with the change pattern of the number of viable cells.…”
Section: Duan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] For these reasons, monitoring of cell therapies is of high clinical relevance and, despite several challenges to overcome, magnetic resonance imaging (MRI) continues to be the method of choice, offering high tissue penetration depth and spatial resolution in comparison with alternative methods. 16,17 Drawbacks of MRI such as low specificity due to unspecific signal from phagocytosed injected cells, dead cells, or local hemorrhage 14,18,19 have been shown to limit the use of MRI for cell imaging in longitudinal studies, and considerable research efforts are devoted to finding alternative/complementary methods. 19,20 With their strong negative contrast in T2-or T2*-weighted MR images, superparamagnetic iron oxide nanoparticles (NPs) are the most common contrast agents used to label cells for MRI cell tracking.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Drawbacks of MRI such as low specificity due to unspecific signal from phagocytosed injected cells, dead cells, or local hemorrhage 14,18,19 have been shown to limit the use of MRI for cell imaging in longitudinal studies, and considerable research efforts are devoted to finding alternative/complementary methods. 19,20 With their strong negative contrast in T2-or T2*-weighted MR images, superparamagnetic iron oxide nanoparticles (NPs) are the most common contrast agents used to label cells for MRI cell tracking. The two most widely used NPs were initially developed and approved by the US Food and Drug Administration (FDA) for liver imaging.…”
Section: Introductionmentioning
confidence: 99%